A new cestode Carpobothrium bombayensis n.sp. (Cestoda - phyllobothridae) from Carchar1as acutvs at bombay (m.s.), india - Khamkar, D D; Mote, A N (International Multidisciplinary Research Journal, 2011)
The present form deals with description of new species of genus Carpobothrium bombayensis n.sp. differs from Carpobohrium megaphallam [1] Subhapradha, 1955 and Carpobothrium subhapradhi [2] Deshmukh and Shinde, 1978 in many characters as in the size of the worms, presence or absence of loculi on the margin of flaps, number of testes, presence or absence of receptaculum seminis, position of uterus and position of ootype.